Advanced QbD-Based Process Optimization of Clopidogrel Tablets with Insights into Industrial Manufacturing Design - Young Woo Bak; Mi Ran Woo; Hyuk Jun Cho; Taek Kwan Kwon; Ho Teak Im; Jung Hyun Cho; Han-Gon Choi (Pharmaceutics)
Background/Objectives: Traditional Quality by Testing (QbT) strategies rely heavily on end-product testing and offer limited insight into how critical process parameters (CPPs) influence product quality. This increases the risk of variability and inconsistent outcomes. To overcome these limitations, this study aimed to implement a Quality by Design (QbD) approach to optimize the manufacturing process of clopidogrel tablets. Methods: A science- and risk-based QbD framework was applied to identify and prioritize key CPPs, intermediate critical quality attributes (iCQAs), and final product CQAs across key unit operations—pre-blending, dry granulation, post-blending, lubrication, and compression. Risk assessment tools and statistical design of experiments (DoE) were used to define proven acceptable ranges (PARs). Results: The study revealed strong correlations between CPPs and CQAs, allowing the definition of PARs and development of a robust control strategy. This led to improved manufacturing consistency, reduced variability, and enhanced process understanding. Conclusions: The QbD approach minimized reliance on end-product testing while ensuring high-quality outcomes. This study offers a novel QbD implementation tailored to the manufacturing challenges of clopidogrel tablets, providing a validated approach that integrates dry granulation CPPs with process-specific CQAs. These results demonstrate the value of QbD in achieving robust pharmaceutical manufacturing and meeting regulatory expectations.